2016
DOI: 10.1155/2016/7548498
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant Blue Dyes in Daily Food: How Could Purinergic System Be Affected?

Abstract: Dyes were first obtained from the extraction of plant sources in the Neolithic period to produce dyed clothes. At the beginning of the 19th century, synthetic dyes were produced to color clothes on a large scale. Other applications for synthetic dyes include the pharmaceutical and food industries, which are important interference factors in our lives and health. Herein, we analyzed the possible implications of some dyes that are already described as antagonists of purinergic receptors, including special Brilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…Importantly, BB-FCF is rapidly excreted from the body and does not seem to display (serious) side-effects either [25]. However, similar to other pharmacological Panx1 inhibitors, the Panx1 specificity of BB-FCF has recently been called into question by studies showing that high concentrations of the dye can directly inhibit P2X receptors [31], and it can thus not be excluded that the in vivo effects of BB-FCF on hemostasis may be partly driven by inhibition of P2X7 receptors expressed in the endothelium. This further emphasizes the need for development of specific Panx1 channel blockers.…”
Section: Blocking Panx1 Channels Delays Hemostasis and Thrombosis In mentioning
confidence: 99%
“…Importantly, BB-FCF is rapidly excreted from the body and does not seem to display (serious) side-effects either [25]. However, similar to other pharmacological Panx1 inhibitors, the Panx1 specificity of BB-FCF has recently been called into question by studies showing that high concentrations of the dye can directly inhibit P2X receptors [31], and it can thus not be excluded that the in vivo effects of BB-FCF on hemostasis may be partly driven by inhibition of P2X7 receptors expressed in the endothelium. This further emphasizes the need for development of specific Panx1 channel blockers.…”
Section: Blocking Panx1 Channels Delays Hemostasis and Thrombosis In mentioning
confidence: 99%
“…Brilliant blue G, also known as Coomassie brilliant blue, is used as a food additive and in the staining of proteins in biomedical applications [23]. It is a purinergic P2X7 receptor antagonist.…”
Section: Rosmentioning
confidence: 99%
“…1, E133) is a reddish-blue triarylmethane water-soluble dye used as a blue colorant. It has reasonable stability when exposed to light, heat and acidic conditions, but it has overall low oxidative stability [162]. This dye is considered harmless and most of the dye is excreted undigested [163].…”
Section: Diet Coloringmentioning
confidence: 99%
“…There is no evidence that this dye in rats or mice is carcinogenic, or neurotoxic [164]. However, this dye can act as purinergic inhibitor without pharmacological selectivity, thereby modulating some organ and tissue functions [162]. In addition, a recent report has demonstrated that this dye showed significant greater absorption in septic patients with reduced intestinal barrier function [165].…”
Section: Diet Coloringmentioning
confidence: 99%
See 1 more Smart Citation